Isolation and characterization of novel Fusobacterium nucleatum bacteriophages - Wang, Yue; Liu, Zhitong; Chen, Qian; Yi, Liqi; Xu, Zihao; Cai, Mufeng; Qin, Jinhong; Zhang, Yan; Du, Guanhuan; Hong, Jie; Guo, Xiaokui; Liu, Chang (Frontiers in Microbiology, 2022)
Fusobacterium nucleatum is a strictly anaerobic, Gram-negative bacterial species that is a member of the commensal flora in the oral cavity and gut. Recent studies suggested that the increase of abundance is associated with the development of various diseases, among which colorectal cancer is of the biggest concerns. Phage therapy is regarded as a potential approach to control the number of F. nucleatum, which may contribute to the prevention and treatment of related diseases. In this study, we isolated five isolates of bacteriophage targeting F. nucleatum. The morphological, biological, genomic and functional characteristics of five bacteriophages were investigated. Transmission electron microscopy revealed that JD-Fnp1 JD-Fnp5 are all myoviruses. The size of the JD-Fnp1 JD-Fnp5 genomes was 180,066 bp (JD-Fnp1), 41,329 bp (JD-Fnp2), 38,962 bp (JD-Fnp3), 180,231 bp (JD-Fnp4), and 41,353 bp (JD-Fnp5) respectively. The biological features including pH and heat stability, host range, growth characteristics of JD-Fnp1 JD-Fnp5 displayed different patterns. Among them, JD-Fnp4 is considered to have the greatest clinical application value. The identification and characterization of JD-Fnp1 JD-Fnp5 provides a basis for subsequent therapeutic strategy exploration of F. nucleatum-related diseases.